SIFO 1986: Volvo and the environment - Swedish Institute of Public Opinion Research; Volvo (Swedish Institute of Public Opinion Research, 1993)
The Swedish Institute of Public Opinion Research (SIFO) carried out this survey at the request of Volvo. Questions were asked about the major problem within the municipality; social structure preferred; worries about food, nuclear power, cancer, AIDS, violence, world starvation, war and environmental pollution; and if a sound environment is preferable to economical growth, high salary and secure jobs. The respondents were also asked about their opinion on having a Volvo car factory in the vicinity, the effects on environment of this industry and if one can trust that the car industry will remain. Other questions dealt with the work environment and health risks at Volvo compared with other industries, the major environmental problems at Volvo and if there are enough knowledge to solve them. Furthermore there were questions about the confidence in different groups information in environmental issues. General opinion of the company Volvo. Background variables include information on gender, place of living, age and occupation.

Svenska institutet för opinionsundersökningar gjorde denna undersökning på begäran av Volvo. Frågor ställdes om största problemen inom kommunen; vilken social struktur som föredrogs, farhågor om mat, kärnkraft, cancer, AIDS, våld, krig och miljöförstöring, om en sund miljö är viktigare en ekonomisk tillväxt, hög lön och säkra jobb. Respondenterna ställdes också frågan om inställning till att ha en Volvo fabrik i sin närhet, effekter på miljön av fabriken och om man kan lita på att bilindustrin ska stanna kvar. Andra frågor handlade om arbetsmiljö och hälsorisker inom Volvo i jämförelse med andra industrier, de största miljöproblemen på Volvo och om det finns tillräckligt med kunskap att lösa dem. Vidare fanns det frågor om förtroendet för olika gruppers information om miljöfrågor. Bakgrundsvariabler inkluderar information om kön, bostadsort, ålder och yrke.
SIFO 1986: Volvo och miljön
Keywords: Environment and conservation; Miljö och naturvård; Business/industrial management and organisation; Företags-/industriledning och organisation; Social Sciences; Samhällsvetenskap